Sociodemographic, clinical, and immunological factors associated with SARS-CoV-2 diagnosis and severe COVID-19 outcomes in people living with HIV: a retrospective cohort study. Issue 11 (November 2021) - Nomah, Daniel K; Reyes-Urueña, Juliana; Díaz, Yesika; Moreno, Sergio; Aceiton, Jordi; Bruguera, Andreu; Vivanco-Hidalgo, Rosa M; Llibre, Josep M; Domingo, Pere; Falcó, Vicenç; Imaz, Arkaitz; Cortés, Cristina; et al.
Summary: Background: Factors affecting outcomes of SARS-CoV-2 infection in people living with HIV are unclear. We assessed the factors associated with SARS-CoV-2 diagnosis and severe outcomes among people living with HIV. Methods: We did a retrospective cohort study using data from the PISCIS cohort of people with HIV in Catalonia (Spain) between March 1 and Dec 15, 2020. We linked PISCIS data with integrated health-care, clinical, and surveillance registries through the Public Data Analysis for Health Research and Innovation Program of Catalonia (PADRIS) to obtain data on SARS-CoV-2 diagnosis, chronic comorbidities, as well as clinical and mortality outcomes. Participants were aged at least 16 years in care at 16 hospitals in Catalonia. Factors associated with SARS-CoV-2 diagnoses and severe outcomes were assessed using univariable and multivariable Cox regression models. We estimated the effect of immunosuppression on severe outcomes (hospital admission for >24 h with dyspnoea, tachypnoea, hypoxaemia, asphyxia, or hyperventilation; or death) using Kaplan-Meier survival analysis. Findings: We linked 20 847 (72·8%) of 28 666 participants in the PISCIS cohort with PADRIS data; 13 142 people had HIV. 749 (5·7%) people with HIV were diagnosed with SARS-CoV-2: their median age was 43·5 years (IQR 37·0–52·7), 131 (17·5%) were female, and 618 (82·5%) were male. 103 people with HIV (13·8%) were hospitalised, seven (0·9%) admitted to intensive care, and 13 (1·7%) died. SARS-CoV-2 diagnosis was more common among migrants (adjusted hazard ratio 1·55, 95% CI 1·31–1·83), men who have sex with men (1·42, 1·09–1·86), and those with four or more chronic comorbidities (1·46, 1·09–1·97). Age at least 75 years (5·2, 1·8–15·3), non-Spanish origin (2·1, 1·3–3·4), and neuropsychiatric (1·69, 1·07–2·69), autoimmune disease (1·92, 1·14–3·23), respiratory disease (1·84, 1·09–3·09), and metabolic disease (2·59, 1·59–4·23) chronic comorbidities were associated with increased risk of severe outcomes. A Kaplan-Meier estimator showed differences in the risk of severe outcomes according to CD4 cell count in patients with detectable HIV RNA (p=0·039) but no differences were observed in patients with undetectable HIV RNA (p=0·15). Interpretation: People living with HIV with detectable HIV viraemia, chronic comorbidities, and some subpopulations could be at increased risk of severe outcomes from COVID-19. These groups should be prioritised in clinical management and SARS-CoV-2 vaccination programmes. Funding: Fundació "la Caixa". Translations: For the Catalan, Spanish and Russian translations of the Summary see Supplementary Materials section.